One new species of Micronephthys Friedrich, 1939 and one new species of Nephtys Cuvier, 1817 (Polychaeta: Phyllodocida: Nephtyidae) from eastern Australia with notes on Aglaophamus australiensis (Fauchald, 1965) and a key to all Australian species - Dixon-Bridges, Kylie; Gladstone, William; Hutchings, Pat (Zootaxa, 2014)
There are currently over 130 described species of Nephtyidae worldwide, with 18 species known from Australian waters belonging to four genera. Two new species are described, Micronephthys derupeli n. sp., and Nephtys triangula n. sp., from Eastern Australia. Descriptions are provided for all species examined. Comments are given about the recent transfer of Nephtys australiensis to Aglaophamus. A key to all Australian species of nephtyids is provided.